The Sustainable Tourism of Lumban Suhi–Suhi Village Samosir after The Pandemic - Eva Gultom (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
The objective of this research is to comprehend the roles of the sustainable tourism toward local community in socio-cultural preservation. In this specific context, this writing specifically focuses on the intentional changes and innovative measures implemented by the local community to promote tourism development, particularly in the aftermath of the pandemic. The research question posed in this study is how the Lumban Suhi Suhi Toruan village can preserve their tourism existence after the pandemic both domestically and internationally. This study utilized qualitative and holistic approaches such as conducting interviews, making observations, or analyzing relevant documents and taking comprehensive notes or the data records for data collection analysis. Lumban Suhi Suhi Village prioritizes the use of media platforms as promotion tool and cultural assimilation towards the pervasive digital changes. The concept of